C/EBPɑ is crucial determinant of epithelial maintenance by preventing epithelial-to-mesenchymal transition - Ana Rita Lourenço (Nature Portfolio, 2020)
In breast cancer TGF-β regulates C/EBPα and can induce epithelial-to-mesenchymal transition (EMT). Here, the authors show that C/EBPα maintains epithelial homeostasis and prevents EMT-mediated tumorigenesis.